Peran Guru IPA MTs Negeri 2 Musi Banyuasin dalam Aktivitas Belajar di Rumah selama Masa Pendemi Covid-19 - Gultom, H. Rahmat (Yayasan Sembilan Pemuda Indonesia, 2021)
The purpose of this study is to describe the role of science instructors at MTs Negeri 2 Musi Banyuasin in home-based learning activities during the covid-19 epidemic. A qualitative technique is used in this research. The study's data was gathered through interviews with Madrasah science teachers in grades VII, VIII, and IX. The findings of this study show that science instructors at MTs N 2 Musi Banyuasin have fulfilled their job as facilitators in ways that are consistent with the indicators, aside from the element of delivering the module via video conference. Teachers are hampered in their function as facilitators by the following factors: 1) many pupils do not have cellphones; 2) some places have a bad internet connection; and 3) purchasing quotas set by parents.